BUILDING CONSUMER ENGAGEMENT THROUGH BRAND STORY TELLING: EXPANDING THE REACH OF BRANDSTORIES - Nandita Mishra, Tanusree Chakraborty, Ashok Natarajan (International Journal of Advanced Science and Technology, 2020)
Brand storytelling is gaining popularity in marketing and brand building. Brand storytelling in simple words is gaining popularity because it creates emotional engagement for listeners and has thus become an important tool in marketing research. Though brand storytelling is gaining this popularity in leaps and bounds, still there is a gap in research in this area. There is hardly any academic research to explain the dynamics of brand storytelling. From marketing point of view, it is important to use a good and compelling story, so it is pertinent to understand why and how storytelling works. With this background the present conceptual paper, bases itself on a review of the literature that looks at story telling from different perspectives, and addresses the role of storytelling in brand building with a holistic view. It deliberates what are the several methods existing for developing brand knowledge among consumers and how it works in creating the emotional engagement and mirroring among listeners. It also tries to explore the various facets of narrative transportation and concludes with an appreciation of the effects of storytelling on brand associations.